Process Optimization of Heating Ovens for Energy Saving and Emission Reduction in Industrial Electrodeposition Painting - Saiful, Rifki; Cahya, Satiya (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2026)
This study discusses efforts to improve the heating oven system in the painting process to increase energy efficiency, reduce operational costs, and lower CO₂ emissions without compromising product quality, including the deactivation of the Recuperative Thermal Oxidizer (RTO) to reduce energy consumption and CO₂ emissions. Prior to improvement, the heating process consisted of three separate stages—pre-heat, heat-up, and keep zone—with a total processing time of approximately 60 minutes. This configuration resulted in annual LNG consumption of 230,866 m³, significantly impacting energy costs and the carbon footprint of the production process. Through process engineering, these stages were simplified into a single rapid-heating phase up to a peak temperature of 180°C, followed by stabilization at 150°C with a total duration of around 18 minutes. This operational redesign reduced cycle time by nearly 50% while optimizing heat distribution inside the oven. The implementation produced significant results: LNG consumption decreased by more than 50%, energy costs dropped from IDR 1.49 billion to IDR 0.71 billion per year, and total CO₂ emissions were reduced from 417.87 tons to 199.56 tons within two years. Product quality evaluation confirmed that the process changes did not affect performance or compliance with specification standards. Additionally, this study recommends further development through data-driven optimization, integration of sensors and IoT for more precise automatic control, and opportunities to utilize renewable energy as part of sustainable manufacturing strategies.